The ROLE OF MICRO SMALL MEDIUM ENTERPRISES (MSMES) GROWTH ON THE INDONESIAN ECONOMY - Hardiyanti, Siti Epa; Wai Si, Hnin (Management Science Research Journal, 2022)
The purpose of this research is to analyze the role of micro, small and medium scale (MSMEs) growth on Indonesian economy. The data has been taken from the data secunder of Biro Pusat Statistik (BPS) and Kementerian Koperasi dan UKM (Kemenkop UKM). The data analyze using regression analyze to determine the role of micro, small and medium scale (MSMEs) growth on Indonesian economy. The results show that a micro, small and medium scale (MSMEs) growth on Indonesian economy have a role but does not have much impact because there are a lot of a factors which have an impact on Indonesian Economy. This result has an implication that the increasing Indonesia’s economic growth on various factors including the increase the number of MSMEs if the increasing of quality products for MSMEs in Indonesia